PERFORMANCE OF SUNFLOWER CULTIVARS IN THREE PLANTING DATES IN NORTH PLATEAU OF SANTA CATARINA STATE - BALBINOT JR., Alvadi Antonio; BACKES, Rogério Luiz; de SOUZA, Adriano Martinho (Scientia Agraria, 2009)
The sunflower planting was stimulated in last years in Santa Catarina State, Brazil, with the aim to produce biodiesel. However, there is lack of information about the adequate cultivars and planting dates to different soil and climatic conditions of this State. The objective of this research was to evaluate the performance of ten sunflower cultivars, cultivated in three planting dates, under the soil and climatic conditions of North Plateau of Santa Catarina State. The cultivars tested were: Aguará 3, Aguará 4, Catissol, Charrua, Dow MG2, Dow M734, Embrapa 122, Helio 358, Helio 360 and IAC Iarama. These cultivars were planted in 20/07/07, 25/09/07 and 18/10/07. The treatments were arranged in a randomized block design, with four replications. There were variations in development cycle, grain yield and other agronomic traits among cultivars. Five cultivars produced more than 2,500 kg ha-1 of grains. July planting date showed the highest average grain yield.